ANALYSIS OF FACTORS INFLUENCING PUBLIC BEHAVIOR INTENTION TO USE MOBILE BANKING DURING THE COVID-19 PANDEMIC - Nabillah Hasna; Agung D. Buchdadi; Muhammad Yusuf (Universitas Nahdlatul Ulama Sidoarjo, 2022)
Test the influence of social influence, perceived ease of use, attitude, and perceived usefulness on the intention to use mobile banking and test the effect of perceived ease of use and perceived usefulness on the attitude of the people of DKI Jakarta during the co-19 pandemic. The sample used in this study is people who have an income and live in DKI Jakarta and who have a bank account. The type of sampling technique used in this study is a convenience sampling technique. This research has involved 204 respondents. Research results: 1) Social influence can positively and significantly influence the intention to use mobile banking during the Covid-19 pandemic. 2) Perceived ease of use can positively and significantly influence the intention to use mobile banking during the Covid-19 pandemic. 3) Attitude can positively and significantly influence the intention to use mobile banking during the Covid-19 pandemic. 4) Perceived usefulness cannot negatively and significantly influence the intention to use mobile banking during the Covid-19 pandemic. 5) Perceived ease of use can influence attitude positively and significantly. 6) Perceived usefulness can influence attitude positively and significantly.